2003
DOI: 10.1098/rspb.2003.2477
|View full text |Cite
|
Sign up to set email alerts
|

Mating in a viscous universe: the race is to the agile, not to the swift

Abstract: Charles Darwin's theory of natural selection has at its focal point the mating success of organisms. Among male animals, large body size is widely seen as the principal determinant of mating success. However, where mating takes place in a three-dimensional arena such as water, the arboreal habitat or air, small size with its concomitant aerobatic advantages might be advantageous. Despite considerable interest, the relationship between aerobatic ability and mating success has not yet been demonstrated in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
3
56
0
1
Order By: Relevance
“…We approximated the position of pulse emissions by bats using the polynomial function [i.e., polynomial approximation for each time series coordinate datum (X, Y, Z) of the calculated sound source]. The flight speed of P. abramus during natural foraging was 9 m/s at a maximum (average, 5 m/s), which is roughly 10 times greater than that of a prey species of the bats (29). At the study site, we also visually observed that dipteran midges took several seconds to fly across an area of a few tens of centimeters.…”
Section: Methodsmentioning
confidence: 99%
“…We approximated the position of pulse emissions by bats using the polynomial function [i.e., polynomial approximation for each time series coordinate datum (X, Y, Z) of the calculated sound source]. The flight speed of P. abramus during natural foraging was 9 m/s at a maximum (average, 5 m/s), which is roughly 10 times greater than that of a prey species of the bats (29). At the study site, we also visually observed that dipteran midges took several seconds to fly across an area of a few tens of centimeters.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanistic explanations for the hypothesis that larger animals perform more poorly in cluttered environments often invoke the predicted decrease in mass-specific force production (and thus acceleration) with increased body size (Vogel, 1994). Maximum mass-specific force production does decrease with body size in bees (Buchwald and Dudley, 2010;Dillon and Dudley, 2004) (although perhaps not across insects more broadly; see Marden, 1987), and there is some evidence that accelerations during free flight decrease with body size in midges (Crompton et al, 2003). Limits to acceleration capacity may reduce an animal's ability to rapidly change its speed and/or direction to avoid collisions, and may also impose limits on flight speed through cluttered environments, as increased speed along a curved path requires higher radial acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…The findings I present have wide application to understanding an aspect of sexual selection where FA affects the biomechanics of mating. This largely neglected type of mating system will reward attention, particularly because technology, in the form of high-speed video recording equipment, offers a tool for close observation of acrobatics in the wild [13,38]. The emphasis on the biomechanical consequences of FA in an aerial mating system is not meant to exclude other possible effects such as direct visual mechanisms, which are known to be important in the biology of some insects [39].…”
Section: Discussionmentioning
confidence: 99%
“…The fertilized female then departs on an egg laying flight. In such an arrangement, sexual selection appears to favor aerobatic ability in the male [13], where access to females may involve competition for a favorable location within the mating swarm [16]. Hence anything that perturbs aerobatic performance tends to reduce mating success and hence male fitness.…”
Section: Some Background On the Biology Of The Chironomid Midgementioning
confidence: 99%
See 1 more Smart Citation